Analisis dan Perancangan Sistem Basis Data Pembelian, Penjualan, dan Persediaan Pada PT Interjaya Surya Megah - Andry Chowanda (Bina Nusantara University, 2010)
The purpose of this paper is to analyze the system of sales, purchases, and inventory of goods at PT Surya Megah Interjaya and designing the database of sales, purchases, and inventories of goods in accordance with the needs of the company, and to design a prototype application. The methodology used to collect information is by fact-finding technique, which conducted a survey, conducting interviews on related parties, and performed an analysis of procedures and corporate documents. As for database design using the methodology of database-life-cycle, which consists of 3 stages, namely: conceptual, logical, and physical database design. Research conducted, resulting conceptual database design, logical, and physical for business processes of sales, purchases, and inventories of goods. A prototype application is developed to build a working model of a database application that allows the designer or user to ensure the final system will be visible and functioning. With the database design and application development, information needs are met quickly and accurately.